A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India - Selvakumar, C.; Chandra, Kailash; Sivaramakrishnan, K. G.; Jehamalar, E. Eyarin (Zootaxa, 2017)
A new species of Thalerosphyrus Eaton 1881 is described based on larvae collected from East Khasi Hills district and East Jaintia Hills district of Meghalaya. Thalerosphyrus meghalayensis Selvakumar & Chandra  n. sp. can be distinguished from other known species of the genus by the following combination of characters: (i) posterolateral expansions of segment VIII always shorter than those of segment VII; (ii) pronotum moderately enlarged laterally; (iii) bristles on the dorsal face of hind femora truncate or round at apex; (iv) hind tibia with a row of thin setae; (v) outer margin of superlinguae evenly covered with long setae ending at apex by minute setae and (vi) posterior margin of tergites with regularly pointed teeth, and numerous microdenticles. A modified larval key is provided for known species of this genus.